Community Integration for After Acquired Brain Injury: A Literature Review - Parvaneh, Shahriar; Ghahari, Setareh; Cocks, Errol (University of Social Welfare and Rehabilitation Sciences, 2014)
Objectives: This paper reviews the current literature on acquired brain injury (ABI) with a focus on ABI burden, importance of community integration, and community integration definitions suggested by the literature. Method: Literature review Results: Acquired brain injury (ABI) is referred to a diverse range of disabilities resulted of injury in different parts of the brain. People with ABI are in face with different aspects of individual, family and social concerns or burdens which directly affect their lives. Although community integration as an ultimate aim of rehabilitation is optimal approach to overcome their consequences, a comprehensive concept of it is always challenging. There are several different definitions for community integration including various aspects of life with ABI. Conclusion: Living with brain injury constitutes an expanded experience of community isolation and consequences which reduces participation and social integration. Community integration is aimed to condense concerns of people with ABI with returning them to community.